Coffee, decaffeinated coffee, and tea consumption in relation to incident type 2 diabetes mellitus: A systematic review with meta-analysis - Huxley, Rachel; Lee, Crystal; Barzi, F.; Timmermeister, L.; Czernichow, S.; Perkovic, V.; Grobbee, D.; Batty, D.; Woodward, M. (American Medical Association, 2009)
Background: Coffee consumption has been reported to be inversely associated with risk of type 2 diabetes mellitus. Similar associations have also been reported for decaffeinated coffee and tea. We report herein the findings of meta-analyses for the association between coffee, decaffeinated coffee, and tea consumption with risk of diabetes. Methods: Relevant studies were identified through search engines using a combined text word and MeSH (Medical Subject Headings) search strategy. Prospective studies that reported an estimate of the association between coffee, decaffeinated coffee, or tea with incident diabetes between 1966 and July 2009. Results: Data from 18 studies with information on 457 922 participants reported on the association between coffee consumption and diabetes. Six (N=225 516) and 7 studies (N=286 701) also reported estimates of the association between decaffeinated coffee and tea with diabetes, respectively. We found an inverse log-linear relationship between coffee consumption and subsequent risk of diabetes such that every additional cup of coffee consumed in a day was associated with a 7% reduction in the excess risk of diabetes relative risk, 0.93 [95% confidence interval, 0.91-0.95]) after adjustment for potential confounders. Conclusions: Owing to the presence of small-study bias, our results may represent an overestimate of the true magnitude of the association. Similar significant and inverse associations were observed with decaffeinated coffee and tea and risk of incident diabetes. High intakes of coffee, decaffeinated coffee, and tea are associated with reduced risk of diabetes. The putative protective effects of these beverages warrant further investigation in randomized trials. ©2009 American Medical Association. All rights reserved.